2018
DOI: 10.1155/2018/4680603
|View full text |Cite
|
Sign up to set email alerts
|

Early Intervention and Nonpharmacological Therapy of Myopia in Young Adults

Abstract: Myopia is a condition of the eye where parallel rays focus in front of, instead of on, the retina, which results in excessive refractive power of the cornea or the lens or eyeball elongation. Studies carried out in recent years show that the etiology of myopia is complex with genetic and environmental factors playing a role. Refraction defects decrease the quality of vision, while progressing myopia can lead to partial loss of vision, which can be particularly dramatic in young adults. Therefore, it is so cruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 70 publications
0
18
0
1
Order By: Relevance
“…Действительно, близорукость встречается более чем у 50 % населения во многих промышленно развитых странах, при этом наблюдается четкая тенденция к увеличению частоты распространения. Например, в некоторых странах Юго-Восточной Азии, в частности в Китае и Южной Корее, распространенность миопии приняла характер своеобразной эпидемии, достигая 85-95 % среди лиц молодого возраста [1][2][3][4]. Исследования, проведенные в последние годы, показывают, что этиология миопии сложна и, несомненно, включает в себя факторы окружающей среды, из которых ведущее место занимает интенсивная зрительная деятельность с электронными средствами отображения информации.…”
Section: Ophthalmology In Russia 2020;17(3):422-428 общие аспектыunclassified
“…Действительно, близорукость встречается более чем у 50 % населения во многих промышленно развитых странах, при этом наблюдается четкая тенденция к увеличению частоты распространения. Например, в некоторых странах Юго-Восточной Азии, в частности в Китае и Южной Корее, распространенность миопии приняла характер своеобразной эпидемии, достигая 85-95 % среди лиц молодого возраста [1][2][3][4]. Исследования, проведенные в последние годы, показывают, что этиология миопии сложна и, несомненно, включает в себя факторы окружающей среды, из которых ведущее место занимает интенсивная зрительная деятельность с электронными средствами отображения информации.…”
Section: Ophthalmology In Russia 2020;17(3):422-428 общие аспектыunclassified
“…Myopia has become a major global public health issue worldwide. Lifestyle risk factors are well known and summarized in recent publications [ 1 , 2 , 3 ]. It has been shown that there is a relation between reading and writing from a short distance and the development of myopia.…”
Section: Introductionmentioning
confidence: 99%
“…The constantly increasing number of eye diseases, as a result of too intensive personal computer work, increases the need for adequate treatment methods. In this context evidence-based complementary methods like acupuncture and/or moxibustion could be potential starting points for early intervention of myopia, which is defined as more than equal to −0.50 diopter (D) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations